Why Mandate Young Borrowers to Contribute to their Retirement Accounts? - Torben M. Andersen; Joydeep Bhattacharya (Center for Economic Studies and ifo Institute (CESifo), 2017)
Many countries, in an effort to address the problem that too many retirees have too little saved up, impose mandatory contributions into retirement accounts, that too, in an age-independent manner. This is puzzling because such funded pension schemes effectively mandate the young, who wish to borrow, to save for retirement. Further, if agents are present-biased, they disagree with the intent of such schemes and attempt to undo them by reducing their own saving or even borrowing against retirement wealth. We establish a welfare case for mandating the middle-aged and the young to contribute to their retirement accounts, even with age-independent contribution rates. We find, somewhat counterintuitively, that even though the young responds by borrowing more that too at a rate higher than offered by pension savings, their life-time utility increases.
Keywords: H55; D91; D03; E60; 330; present-biased preferences; mandatory pensions; pension offsets; crowding out